Challenges Confronting the Practice of Nursing in Singapore - Gek Phin Chua (Elsevier, 2020)
Singapore, a young nation like many developed countries, faced a shortage of nurses. Attempts to resolve the workforce shortage through the employment of foreign nurses started in the mid-1980s. Over the years, workforce recruitment from traditional sources nearby, namely Malaysia and Philippines, has expanded to include nurses from countries such as People Republic of China, India, and Myanmar. Attempts have also been made to train, recruit, and retain local nurses such as improving working conditions and remunerations, raising the profile of nursing, improving career recognition and progression, and encouraging nonpracticing nurses back to the workforce. However, the institutions' and the government's attempts to ameliorate the nursing shortage were met with limited success. Even with the recruitment of foreign nurses, the shortage of workforce persists. The shortage is compounded by the three major health-care challenges confronting Singapore: (1) rapid growth in population; (2) rapid aging of the population; and (3) increasing burden of chronic diseases. As the population continues to grow and as more of the population ages, as life expectancy increases and the burden of chronic diseases increases, not only will the demand for nurses continue, but the intensity and the nursing care they require will also increase. This article describes the challenges confronting the practice of nursing in Singapore and their implications. Although these challenges are daunting, they offer nursing the unprecedented opportunities to shape health-care delivery systems and increase nursing influences everywhere across settings and along the delivery continuum.